Regulacja prawna transplantacji w ustawodawstwie europejskim - Urban-Dechnik, Hanna (Europejskie Stowarzyszenie Studentów Prawa ELSA Poznań, 2013)
In recent years, a tormenting phenomenon can be observed related to the decreasing number of transplants performed due to the limited amount of patron organs. This fact has become an opportunity to analyse the European Union’s regulations of transplantations. The achievements of the Council of Europe and the European Union in terms of organ donation and transplantation has been presented in detail with a conclusion heading towards the dangerous commercialization process of transplantations. This article presents also the standards developed by the European Union in regard to transplantology which clearly supports the fact that organ donation should be on non-profit and altruistic basis excluding commercial aspects.
Legal framework of transplantations in European Union legislation
Keywords: European Union law; transplantology; human organs